Study of damage to the cardiovascular system in patients with systemic scleroderma - Nabiyeva A.X; Bekenova G.T (Genius Publishing Group, 2022)
The investigation enrolled 125 patients with SS and 50 sexand age-matched, apparently healthy individuals included in a control group. Standard electrocardiography was performed in all and EchoCG – in 121 patients. The Systematic Coronary Risk Evaluation (SCORE) scale was used to assess the risk of fatal CVD in 100 patients with SS and in 47 control individuals within 10 years.
Keywords: Evaluation; fatal; electrocardiography; individuals